Global infection prevention gaps, needs, and utilization of educational resources: A cross-sectional assessment by the International Society for Infectious Diseases - Desai,AN; Ramatowski,JW; Lassmann,B; Holmes,A; Mehtar,S; Bearman,G (International Journal of Infectious Diseases, 2019)
OBJECTIVE: The Guide to Infection Control in the Hospital (Guide) is an open access resource produced by the International Society for Infectious Diseases (ISID) to assist in the prevention of infection acquisition and transmission worldwide. A survey was distributed to 8055 current Guide users to understand their needs. METHODS: The survey consisted of 48-questions regarding infection prevention and control (IPC) availability and needs. Dichotomous questions, Likert scale-type questions, and open-and closed-ended questions were used. RESULTS: Respondents (n=1121) from 194 countries and six WHO regions participated in the survey. 43% (488) identified as physicians. Personal protective equipment (PPE) availability, training, and antimicrobial susceptibility testing varied between regions. Only 11% of respondents from low-income countries reported consistent access to respiratory equipment, 12% to isolation gowns, 4% to negative pressure rooms or personnel trained in IPC, and 20% to antimicrobial resistance testing. This differed significantly to high and upper middle-income resource settings (p<0.05). 80% of all respondents used smartphones or tablets at the workplace. CONCLUSIONS: This survey demonstrates varied access to IPC equipment and training between high and low-income settings worldwide. Our results demonstrated many respondents across all regions utilize mobile technology, providing opportunities for rapid distribution of resource specific, up-to-date IPC content.